Financial analysis of layer industry in Pulau Pinang, Malaysia - Rokimi, Nabilah Adilah (2018)
The egg industry in our country has been rapidly grown and turn into one of the modern industries. This is due to the large productions units, a various range of tailor made eggs, and egg products produced in market to meet customer needs. About more than 40 million eggs are produced in industry per day . This research was conducted to asses financial assessment of layer farms in Pulau Pinang, Malaysia and to described the existing cost attribute of layer farms in Pulau Pinang, Malaysia. Financial assessment important to the new entrepreneur that involves in this layer industry, by using this assessment they can assess the liquidity, profitability, financial strength, and efficiency of the business. This helps greatly in making good investment decisions. On the other hand, takes the broader picture into view by including various economy and environmental variables into account. This helps the entrepreneur in predicting the future prospects of an organization. This research was conducted on 26 farmers which come from various age, educational background and experience. The data was collected from Institute of Agriculture and Food Policy Studies. The data include the farmer’s information and cost involving the layer farms. The data is acquired by finding the costing analysis and capital budgeting analysis and run manually using Microsoft Excel. Overall, the research showed the most high cost involves in layer industry is feed cost and the layer project is economically and financially viable.